2017
DOI: 10.4184/asj.2017.11.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Driving Safety after Spinal Surgery: A Systematic Review

Abstract: This study aimed to assess driving reaction times (DRTs) after spinal surgery to establish a timeframe for safe resumption of driving by the patient postoperatively. The MEDLINE and Google Scholar databases were analyzed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) Statement for clinical studies that investigated changes in DRTs following cervical and lumbar spinal surgery. Changes in DRTs and patients' clinical presentation, pathology, anatomical level affected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Compared to the healthy controls' BRT (535.6 ±118.6ms), the patients' BRT was significantly slower at two weeks (p = 0.003) but not different at four weeks (p = 0.473) (Cross-sectional comparison, Hypothesis 2, Table 2 ). At this point in time, the BRT was also well below what was recommended by road authorities (70 0-150 0ms) [17][18][19][20][21] . Notwithstanding the genuine slow brakers (n = 4, 13,3%), who never successfully achieved sufficient BRTs, all patients (n = 13 out of n = 13) with an AOFAS-AHS score of more than 80 points had sufficient BRTs within two weeks (100%) (Hypothesis 3).…”
Section: Resultsmentioning
confidence: 77%
“…Compared to the healthy controls' BRT (535.6 ±118.6ms), the patients' BRT was significantly slower at two weeks (p = 0.003) but not different at four weeks (p = 0.473) (Cross-sectional comparison, Hypothesis 2, Table 2 ). At this point in time, the BRT was also well below what was recommended by road authorities (70 0-150 0ms) [17][18][19][20][21] . Notwithstanding the genuine slow brakers (n = 4, 13,3%), who never successfully achieved sufficient BRTs, all patients (n = 13 out of n = 13) with an AOFAS-AHS score of more than 80 points had sufficient BRTs within two weeks (100%) (Hypothesis 3).…”
Section: Resultsmentioning
confidence: 77%
“…Most (n=13, 61.9%) patients who passed the DARP did so at the 6-week mark, which corresponded to statistically significant improvements in NDI, mJOA scores, and functional strength of the cervical spine flexors. Previous studies utilizing BRT have demonstrated nonstatistically significant increases1,3,8 or reductions2 in BRT after cervical spinal surgery and recommend a return to driving after discharge from the hospital. Most authors1,8,41,42 do, however, caution against the use of BRT exclusively for determining the driving ability and recommend evaluating the patient holistically due to the complex nature of driving as well as the medicolegal ramifications of certifying a patient for driving when they are not clinically ready.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies utilizing BRT have demonstrated nonstatistically significant increases1,3,8 or reductions2 in BRT after cervical spinal surgery and recommend a return to driving after discharge from the hospital. Most authors1,8,41,42 do, however, caution against the use of BRT exclusively for determining the driving ability and recommend evaluating the patient holistically due to the complex nature of driving as well as the medicolegal ramifications of certifying a patient for driving when they are not clinically ready. Kelly et al,27 utilizing the driving subsection of the NDI, reported that 49.6% of patients reported moderate to severe difficulty in driving preoperatively, with the majority of patients demonstrating little to no driving difficulty at 6 weeks postoperation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation